Assessment of Acute Toxicity and Lethal Dose of Prodigosin in Mice - maryam niakani; hassan malekinejad; ahmad majd; parviz pakzad (Fasa University of Medical Sciences, 2020)
Background & Objective: Acute toxicity assessment is the first priority in the determination of any related risk to the biologically unknown chemicals to human and animals. LD50 determination as an accepted model of acute toxicity assay in animal models for a new drug in clinical trials is one of the important requirements of the drug launching process. Prodigiosin is a substance extracted from Serratia marcescens and has antitumor and antifungal activities. Thus, in this study, acute toxicity of prodigiosin was determined using the lowest number of laboratory animals. Materials & Methods: In this experimental study, different doses of prodigiosin were administered intraperitoneally in male mice. Twenty four hours after injection, alongside examining behavior of the animals receiving the prodigiosin, some organs including the heart, liver, kidney, spleen, intestine and lung were sampled, and after paraffin block preparation and microtome cutting, they were stained with hematoxylin-eosin and examined by light microscopy. Results: The results of this study indicated that LD50 for prodigiosin is 4500 mg / kg, when administered intraperitoneally and histopathological findings indicate very slight and minor damage to the liver, kidney and spleen, while no remarkable damage on other organs including the heart, lung and intestine was observed. Conclusion: Based on the results of current study and estimated LD50 level, it is suggested that prodigiosin can be categorized as a safe compound with the least histopathological impact on the vital organs.